CULTURAL LANDSCAPE BY THE SEA AS COMMONS: COLLABORATIVE PLANNING FOR THE METROPOLITAN WATERFRONT OF NAPLES - Clemente, Massimo; Giovene di Girasole, Eleonora; Cannatella, Daniele; Martucci, Casimiro (BDC. Bollettino Del Centro Calza Bini, 2015)
Cities by the sea are special “historic cultural landscapes”, and maritime identity acquires new meanings for the touristic enhancement of urban coastal areas and it may represent a driver for socio-economic development. New strategies to stop deterioration in urban coastal areas should take place both through a conscious and evolved the type of tourism both through innovative processes. The paper analyzes some interventions of waterfront regeneration and tourism development in some seaside cities involving their maritime culture. New collaborative models of lateral participation took place as alternatives to the vertical models: “collaborative commons” might start its process for the touristic enhancement and regeneration of the metropolitan coast of Naples. Keywords: maritime identity, sustainable tourism, collaborative urban regeneration Cities by the sea are special “historic cultural landscapes”, and maritime identity acquires new meanings for the touristic enhancement of urban coastal areas and it may represent a driver for socio-economic development. New strategies to stop deterioration in urban coastal areas should take place both through a conscious and evolved type of tourism both through innovative processes. The paper analyzes some interventions of waterfront regeneration and tourism development in some seaside cities involving their maritime culture. New collaborative models of lateral participation took place as alternatives to the vertical models: “collaborative commons” might start its process for the touristic enhancement and regeneration of the metropolitan coast of Naples. Keywords: maritime identity, sustainable tourism, collaborative urban regeneration